Research on International Layout and Regional Brand IP Construction of China’s Ceramic Industry under the RCEP Framework - Jin, Mengting (Pinnacle Academic Press Proceedings Series, 2026)
The Regional Comprehensive Economic Partnership (RCEP) creates unprecedented opportunities for China’s ceramic industry to expand its global presence and strengthen regional brand influence within an integrated Asia-Pacific market. However, intensified market competition, heterogeneous consumer preferences, cultural differences, and persistent challenges in intellectual property protection continue to constrain strategic internationalisation. This paper examines how the RCEP framework can support China’s ceramic industry in designing an effective international layout and constructing distinctive regional brand intellectual property (IP). By integrating trade policy analysis, market positioning strategies, and brand IP management, the study develops a comprehensive analytical framework to guide enterprises and industrial clusters in leveraging tariff reductions, rules of origin, and trade facilitation measures. Case studies of representative ceramic clusters, including Jingdezhen and Foshan, are used to illustrate how institutional advantages, cultural branding, design innovation, and IP protection mechanisms jointly contribute to competitive positioning and value upgrading. The research further discusses the coordination between industrial policy, regional cooperation, and enterprise-level branding strategies under RCEP. The findings highlight the synergy between international trade liberalisation and cultural brand building in enhancing the global competitiveness, value chain status, and sustainable development capacity of China’s ceramic industry, and provide policy and managerial implications for other traditional manufacturing sectors seeking regional brand IP construction.